STEM Integrated Vocational Program: Urgency in Improving the Comprehension Abilities of Students with Mild Intellectual Disability - Purnamawati; Mumpuniarti (PLD UIN Sunan Kalijaga, 2025)
Students with intellectual disabilities require special attention in learning to overcome conceptual and procedural challenges. This study aimed to examine the impact of a STEM-integrated vocational program on the comprehension abilities of students with mild intellectual disabilities. Using a quasi-experimental design, the research involved 50 purposively selected students at SLB Negeri Pembina Yogyakarta. The intervention group received STEM-integrated instruction, while the control group followed conventional vocational learning. The results indicated that although the proportion of students achieving scores above the Minimum Competency Criteria did not increase significantly, there was a significant improvement in comprehension abilities among the experimental group compared to the control group. These findings suggest that integrating STEM approaches into vocational education can effectively enhance comprehension skills, supporting more adaptive and inclusive learning outcomes for students with intellectual disabilities. Siswa dengan disabilitas intelektual memerlukan perhatian khusus dalam belajar untuk mengatasi tantangan konseptual dan prosedural. Penelitian ini bertujuan untuk menguji dampak program kejuruan terintegrasi STEM terhadap kemampuan pemahaman siswa dengan disabilitas intelektual ringan. Menggunakan desain kuasi-eksperimental, penelitian ini melibatkan 50 siswa yang dipilih secara sengaja di SLB Negeri Pembina Yogyakarta. Kelompok intervensi menerima instruksi terintegrasi STEM, sementara kelompok kontrol mengikuti pembelajaran kejuruan konvensional. Hasilnya menunjukkan bahwa meskipun proporsi siswa yang mencapai skor di atas Kriteria Kompetensi Minimum tidak meningkat secara signifikan, ada peningkatan yang signifikan dalam kemampuan pemahaman di antara kelompok eksperimen dibandingkan dengan kelompok kontrol. Temuan ini menunjukkan bahwa mengintegrasikan pendekatan STEM ke dalam pendidikan kejuruan dapat secara efektif meningkatkan keterampilan pemahaman, mendukung hasil belajar yang lebih adaptif dan inklusif bagi siswa dengan disabilitas intelektual.